The damage and failure mechanism of the concrete subjected to shaped charge loading. (December 2017) - Xu, Xiang-zhao; Ma, Tian-bao; Ning, Jian-guo
Abstract: In this paper, the experiments of the large-size shaped charge jet penetration in concrete target were carried out. Then, the concrete target was cut off to obtain the internal structure and measure the shape of the penetration hole. Moreover, the cube concrete samples with the sizes of 100 mm length in different location of the concrete target were incised, and the material compressive strength was test by the material testing machine. The test results show that the material strength of the concrete target is enhanced with the increase of the distance to the penetration hole. Therefore, the damage of concrete target can be rough evaluated according to the compressive strength of the concrete samples. Based on the test results, the damage factor was added in the dynamic constitutive, which can describe mechanical behavior of concrete subjected to intensive impact loading was proposed. In this model, the concrete is assumed to be homogenous and consecutive in macroscopically. The results of the model were compared with the experimental results and the results which not considering the damage factor. The comparing results show that the model can be used to describe the dynamic mechanical behavior of concrete. Highlights: A dynamic constitutive which can describe mechanical behavior of concrete was proposed subjected to impact loading. A heavy-caliber shaped charge structure was designed and the corresponding experiments were carried out. The internal damage of the concrete was observed and the shape of the penetration hole was measured. The damage of concrete target was evaluated and the corresponding decreasing laws of the damage degree were obtained.